TWO-PHASE FLUID INTERFACIAL INSTABILITIES INDUCED BY AXISYMMETRIC ROTATION UNDER THE INFLUENCE OF AN EXTERNALLY APPLIED MAGNETIC FIELD MAGNETIC FIELD - Clement, Bobby (2023)
In this thesis, we discuss the use of a superconducting solenoid magnet to investigate radial interfacial instabilities between two rotating immiscible, incompressible fluids of differing density. The magnetic field produced by the solenoid magnet is used to induce a radial body force on diamagnetic and paramagnetic fluids, providing an effective acceleration in the radial direction that affect the instability growth rate at the interface. The applied rotation is then controlled to induce instability for various wavenumbers, analogous with horizontal gravitational instability. The investigation is focused on a circular Hele-Shaw cell containing two fluids of non-equal density that occupy a small gap between two solid flat plates.